Catalytic Oxidation of Methane to Oxygenated Products: Recent Advancements and Prospects for Electrocatalytic and Photocatalytic Conversion at Low Temperatures. Issue 23 (27th October 2020) - Sher Shah, Md. Selim Arif; Oh, Cheoulwoo; Park, Hyesung; Hwang, Yun Jeong; Ma, Ming; Park, Jong Hyeok
Abstract: Methane is an important fossil fuel and widely available on the earth's crust. It is a greenhouse gas that has more severe warming effect than CO2 . Unfortunately, the emission of methane into the atmosphere has long been ignored and considered as a trivial matter. Therefore, emphatic effort must be put into decreasing the concentration of methane in the atmosphere of the earth. At the same time, the conversion of less valuable methane into value‐added chemicals is of significant importance in the chemical and pharmaceutical industries. Although, the transformation of methane to valuable chemicals and fuels is considered the "holy grail, " the low intrinsic reactivity of its CH bonds is still a major challenge. This review discusses the advancements in the electrocatalytic and photocatalytic oxidation of methane at low temperatures with products containing oxygen atom(s). Additionally, the future research direction is noted that may be adopted for methane oxidation via electrocatalysis and photocatalysis at low temperatures. Abstract : Methane, a natural and potential greenhouse gas, is widely available. Conversion of methane can decrease global warming and warrant future energy and fuel supply. Herein, recent advancements of photocatalytic and electrocatalytic conversion of methane to oxygenates at low temperatures are summarized. Techniques to overcome challenges in methane oxidation are discussed. Prospects of methane oxidation by photocatalysis and electrocatalysis are demonstrated.